2012
DOI: 10.1021/am302704a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide as a Quencher for Fluorescent Assay of Amino Acids, Peptides, and Proteins

Abstract: Understanding the interaction between graphene oxide (GO) and the biomolecules is fundamentally essential, especially for disease- and drug-related peptides and proteins. In this study, GO was found to strongly interact with amino acids (tryptophan and tyrosine), peptides (Alzheimer's disease related amyloid beta 1-40 and type 2 diabetes related human islet amyloid polypeptide), and proteins (drug-related bovine and human serum albumin) by fluorescence quenching, indicating GO was a universal quencher for tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
145
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(160 citation statements)
references
References 38 publications
15
145
0
Order By: Relevance
“…To understand the roles of GO in interacting with biomolecules, Li et al 52 studied the effect of GO as a quencher on the fluorescent assay of amino acids, peptides, and proteins. The work started with the fluorescence quenching of L-Tyrosin Tyr and L-tryptophan Trp by GO.…”
Section: Two Dimensional Carbon Nanomaterialsmentioning
confidence: 99%
“…To understand the roles of GO in interacting with biomolecules, Li et al 52 studied the effect of GO as a quencher on the fluorescent assay of amino acids, peptides, and proteins. The work started with the fluorescence quenching of L-Tyrosin Tyr and L-tryptophan Trp by GO.…”
Section: Two Dimensional Carbon Nanomaterialsmentioning
confidence: 99%
“…GO also quenches tryptophan or tyrosine containing peptides and proteins and electrostatic interaction plays an important role during quenching. Static quenching is the main mechanism, combined with Förster resonance energy transfer or dynamic quenching (Li et al, 2012). This is the rationale behind the use of GO together with a fluorescence dye in various IA formats.…”
Section: Immunosensing Procedures For Ceamentioning
confidence: 99%
“…S2D, no peak shift of the spectra was observed, indicating BLA fluorescence quenching by GOns. In fact, it has already been reported that GO is a universal quencher, and it interacts with proteins through static as well as dynamic quenching [46].…”
Section: Circular Dichroism (Cd) and Trp Fluorescence Spectroscopy Ofmentioning
confidence: 99%